3D printed heterogeneous hybrid hydrogel scaffolds for sequential tumor photothermal-chemotherapy and wound healing. (22nd August 2022) - Xu, Langtao; Chen, You; Zhang, Peng; Tang, Junjie; Xue, Yifan; Luo, Hongsheng; Dai, Rui; Jin, Jinlong; Liu, Jie
Abstract : A 3D printed heterogeneous hybrid hydrogel scaffold was fabricated for sequential tumor photothermal-chemotherapy and wound healing, which could be a potential technique for preventing tumor recurrence and promoting wound healing following surgery. Abstract : Surgical resection remains the mainstay of melanoma treatment. However, due to the difficulties in controlling tumor recurrence and wound healing simultaneously, high postoperative recurrence rates and wound reconstruction remain the most significant challenges. As a result, a heterogeneous hybrid hydrogel scaffold was designed in this work to achieve sequential photothermal therapy and chemotherapy for melanoma recurrence inhibition and wound healing. A 3D printing platform was used to create a SA-GG@PDA hybrid hydrogel scaffold, which was prepared from a hybrid bioink consisting of sodium alginate (SA), gellan gum (GG), and polydopamine nanoparticles (PDA NPs). The printability, biocompatibility, and mechanical qualities of the hybrid bioink were all satisfactory. PDA NPs were generated in situ in the hybrid bioink, providing superior photothermal effects to the scaffold. After coating with a thermosensitive gelatin hydrogel loaded with the chemotherapeutic drug doxorubicin (DOX), the heterogeneous hydrogel scaffold could accelerate drug release under photothermal triggering and achieve photothermal-chemotherapy to suppress tumor cell proliferation and recurrence after surgical resection. Subsequently, the printed porous hybrid hydrogel scaffold enhanced HUVEC proliferation and migration, as well as tissue ingrowth, promoting wound healing following surgery. In the same mouse model, the sequential treatment with the heterogeneous SA-GG@PDA + DOX hydrogel scaffold was tested. The fabrication of the heterogeneous SA-GG@PDA + DOX hydrogel scaffold with multifunctional capabilities seemed to be a potential technique for preventing tumor recurrence and promoting wound healing following surgery.